Microarray patch for HIV prevention and as a multipurpose prevention technology to prevent HIV and unplanned pregnancy: an assessment of potential acceptability, usability, and programmatic fit in Kenya - Gachigua, Sammy Gakero; Karuga, Robinson; Ngunjiri, Anne; Jarrahian, Courtney; Coffey, Patricia S.; Kilbourne-Brook, Maggie; Otiso, Lilian (Frontiers in Reproductive Health, 2023)
Background: Microarray patches (MAPs), a novel drug delivery system, are being developed for HIV pre-exposure prophylaxis (PrEP) delivery and as a multipurpose prevention technology (MPT) to protect from both HIV and unintended pregnancy. Prevention technologies must meet the needs of target audiences, be acceptable, easy to use, and fit health system requirements. Methodology: We explored perceptions about MAP technology and assessed usability, hypothetical acceptability, and potential programmatic fit of MAP prototypes using focus group discussions (FGD), usability exercises, and key informant interviews (KII) among key populations in Kiambu County, Kenya. Adolescent girls and young women AGYW, female sex workers (FSW), and men who have sex with men (MSM) assessed the usability and acceptability of a MAP prototype. Male partners of AGYW/FSW assessed MAP acceptability as partners of likely users. We analyzed data using NVivo, applying an inductive approach. Health service providers and policymakers assessed programmatic fit. Usability exercise participants applied a no-drug, no-microneedle MAP prototype and assessed MAP features. Results: We implemented 10 FGD (4 AGYW; 2 FSW; 2 MSM; 2 male partners); 47 mock use exercises (19 AGYW; 9 FSW; 8 MSM; 11 HSP); and 6 policymaker KII. Participants reported high interest in MAPs due to discreet and easy use, long-term protection, and potential for self-administration. MAP size and duration of protection were key characteristics influencing acceptability. Most AGYW preferred the MPT MAP over an HIV PrEP-only MAP. FSW saw value in both MAP indications and voiced need for MPTs that protect from other infections. Preferred duration of protection was 1–3 months. Some participants would accept a larger MAP if it provided longer protection. Participants suggested revisions to the feedback indicator to improve confidence. Policymakers described the MPT MAP as “killing two birds with one stone,” in addressing AGYW needs for both HIV protection and contraception. An MPT MAP is aligned with Kenya’s policy of integrating health care programs. Conclusions: MAPs for HIV PrEP and as an MPT both were acceptable across participant groups. Some groups valued an MPT MAP over an HIV PrEP MAP. Prototype refinements will improve usability and confidence.